Factors influencing credit card spending behaviour among gen Y employees in Zuellig pharma Sdn. Bhd. / Fatin Atasha Md Zaki - Md Zaki, Fatin Atasha (Faculty of Business Management, 2015)
The study aims to identify the factors influencing credit card spending behaviour among Gen Y employees in Zuellig Pharma Sdn. Bhd. The objectives of this study were to identify the level of credit card spending behaviour, the relationship between independent variables (benefits given by bank and attitude towards money); and dependent variable (credit card spending behaviour) and what is the significant predictor variable of credit card spending behaviour among Gen Y employees in Zuellig Pharma Sdn. Bhd. Moreover, the study employed survey research design and primary data was collected through questionnaires with 123 respondents were selected. Eventually, the findings of this research shows significant relationship between both the independent variables (benefits given by bank and attitude towards money); and dependent variable (credit card spending behaviour). It was acknowledged that the most significant predictor variable of credit card spending behaviour among Gen Y employees in Zuellig Pharma Sdn. Bhd. was attitude towards money. However, this study have recommended, since benefits given by bank are found to influence credit card spending behaviour as well, the issuing banks and nonbanks must continuously examine the incentives provided and payment policies enforced in order to attract applicants and ensure usage. As for future researchers, they may complement other independent variables, considering a bigger sample size and retest the survey instrument in different countries or states to extend the understanding of credit card spending behaviour for the forthcoming.